2020
DOI: 10.1055/s-0040-1718921
|View full text |Cite
|
Sign up to set email alerts
|

Current and Future Surgical and Interventional Management Options for Adenomyosis

Abstract: Historically, hysterectomy has been the recommended treatment for patients with adenomyosis. However, in the past two decades, various uterine-sparing treatment methods have emerged. These range from excisional techniques such as adenomyomectomy or wedge resection to uterine artery embolization, radiofrequency thermal ablation, hysteroscopic excision, endometrial ablation, and high-intensity focused ultrasound. While largely investigative for the treatment of adenomyosis, these procedures have demonstrated imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Although future fertility is often desired by women choosing these options, data regarding reproductive outcomes remain limited. Uterine artery embolization is the most well-studied intervention for adenomyosis and effectively decreases heavy menstrual bleeding and dysmenorrhea; however, approximately 25% of patients will undergo subsequent hysterectomy due to persistent symptoms . Pregnancy after uterine artery embolization is not generally recommended based on studies that demonstrated higher rates of obstetric complications, including miscarriage and postpartum hemorrhage.…”
Section: Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Although future fertility is often desired by women choosing these options, data regarding reproductive outcomes remain limited. Uterine artery embolization is the most well-studied intervention for adenomyosis and effectively decreases heavy menstrual bleeding and dysmenorrhea; however, approximately 25% of patients will undergo subsequent hysterectomy due to persistent symptoms . Pregnancy after uterine artery embolization is not generally recommended based on studies that demonstrated higher rates of obstetric complications, including miscarriage and postpartum hemorrhage.…”
Section: Treatmentmentioning
confidence: 99%
“…Similarly, endometrial ablation, which seeks to destroy the endometrium, diminishes bleeding and pain, but subsequent pregnancy is not recommended. Excisional procedures, such as adenomyomectomy, uterine wedge resection, and hysteroscopic excision, have shown promise in improving symptoms to varying degrees, with up to 60% of women achieving subsequent pregnancy . These techniques of focal excision of both diffuse and focal adenomyosis are not commonly used, but show promise over more global uterine procedures for women seeking to preserve fertility.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the minimally invasive therapies is image-guided thermal ablation that destroys the lesions by a rapid temperature rise. Currently, there are several thermal energy sources used in clinical practice, involving high-intensity focused ultrasound (HIFU), percutaneous microwave ablation (PMWA) and radiofrequency ablation (RFA) [8]. HIFU ablation is performed under the guidance of ultrasound or magnetic resonance imaging (MRI) without the use of an antenna or electrode.…”
Section: Introductionmentioning
confidence: 99%